Request strategies in email communication: The case of Indonesian graduate students in Japan - Rezky Pratiwi Balman; Lee Sangmok; Narahiko Inoue (Universitas Syiah Kuala, 2020)
While research in speech act has received a lot of academic attention, how requesting strategies are performed in email communication among non-native speakers in a broader cultural context remains scarcely sufficient. This study investigates requesting strategies employed by non-native English-speaking students (i.e. Indonesians) to non-native English university professors (i.e. Japanese) through the medium of email. It further sought whether the strategies performed are different between low and high imposition requests. This study applied both qualitative and quantitative approaches using a corpus of 56 authentic emails. The data were analyzed using a modified version of the request strategies framework of Blum-Kulka et al.’s (1989) Cross-Cultural Speech Act Realization Project (CCSARP) contrived by Economidou-Kogetsidis (2011). The results show a pattern of different requesting strategies emerged in accordance with the imposition of the requests the students make. While Conventionally Indirect Strategy in the form of query preparatory is found to be favored when writing low imposition email requests, this strategy is not appeared to be preferred when students write high imposition requests. Instead, Indonesian students tend to employ a great deal of Hint Strategies and let the professors interpret their intention in the emails.